NA (NEED ANALYSIS) AS A FUNDAMENTAL PRINCIPLE IN ORGANIZING AN ESP (ENGLISH FOR SPECIFIC PURPOSES) COURSE - Davron Abdullaev, Davron Abdullaev (Журнал иностранных языков и лингвистики, 2021)
This article attempts to explain the importance of NA in organizing English language classes for students of non-philological majors.